Glucose biosensor based on multisegment nanowires exhibiting reversible magnetic control - Gerola, Gislaine P. [UNESP]; Takahashi, Giovanna S. [UNESP]; Perez, Geraldo G. [UNESP]; Recco, Lucas C. [UNESP]; Pedrosa, Valber A. [UNESP] (Elsevier B.V., 2014)
We describe the amperometric detection of glucose using oriented nanowires with magnetic switching of the bioelectrochemical process. The fabrication process of the nanowires was prepared through controlled nucleation and growth during a stepwise electrochemical deposition, and it was characterized using scanning electron microscopy. Cyclic voltammetry and amperometry were used to study the magnetoswitchable property; this control was accomplished by changing the surface orientation of nanowires. Under the optimal condition, the amperometric response was also linear up to a glucose concentration of 0.1-16.0 mmol L-1 with a sensitivity of 81 mu A. mM(-1). The detection limit was estimated for 4.8 x 10(-8) mol L-1, defined from a signal/noise ratio of 3. It also exhibits good reproducibility and high selectivity with insignificant interference from ascorbic acid, acetoaminophen, and uric acid. The resulting biosensor was applied to detect the blood sugar in human serum samples without any pretreatment, and the results were comparatively in agreement with the clinical assay. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biosensor; Nanowires orientation; Reversible modulation